Diagnostic accuracy of core biopsy in patients presenting with axillary lymphadenopathy and suspected non-breast malignancy. Issue 7 (July 2021) - Edirisooriya, Monisha; Jack, Wilma; Twelves, Dominique; Royds, Jennifer; Scott, Fiona; Mason, Nicola; Turnbull, Arran; Dixon, J. Michael
Abstract: Introduction: Excision biopsy has been the investigation of choice for patients presenting with pathological axillary lymphadenopathy without a breast abnormality. Core biopsy of nodes can provide sufficient tissue for diagnosis and has advantages in terms of morbidity and speed of diagnosis. This study evaluates the diagnostic accuracy of core biopsy in patients presenting with axillary lymphadenopathy. Methods: Between 2009 and 2019, 165 patients referred to the Edinburgh Breast Unit had a total of 179 axillary lymph node core biopsies. Results: 152 (92%) of the 165 initial core biopsies were deemed to contain adequate nodal tissue. Core biopsy correctly established malignancy in 75 of the 78 patients with haematological malignancy (96%) and in all 28 patients with metastatic carcinoma (100%) and correctly diagnosed benign changes in 49 of 57 (86%) patients with benign conditions. There were no false positives and no false negatives. In 67 (85.9%) of the 78 patients with haematological malignancy there was sufficient material in the first core biopsy to allow the pathologist to make an actionable diagnosis and not ask for more tissue sampling prior to treatment. There were no complications of core biopsy. On follow up, none of the patients with benign cores has been shown to have malignancy in the axilla and none with lymphoma had their initial disease incorrectly classified. Conclusions: This study shows that core biopsy is now the investigation of choice for patients presenting with axillary lymphadenopathy even in those suspected as having lymphoma.